1
$\begingroup$

For example

\begin{equation} \begin{aligned} \lim_{n \to \infty} \left(1 + \frac{1}{ \frac{n-1}{2}} \right)^{n} &= \lim_{n \to \infty} \left(1 + \frac{1}{ \frac{n-1}{2}} \right)^{\frac{n-1}{2}\cdot\frac{2}{n-1}\cdot n} \\ &= \lim_{n \to \infty} \left(\lim_{n \to \infty} \left(1 + \frac{1}{ \frac{n-1}{2}} \right)^{\frac{n-1}{2}} \right)^{\frac{2}{n-1}\cdot n} \\&= \lim_{n \to \infty} e^{\frac{2n}{n-1}} = e^{2} \end{aligned} \end{equation}

In general we can not move the limit under a non constant exponent and evaluate the exponent limit later

$$ e = \lim_{n \to \infty} \left( 1 + \frac{1}{n} \right)^n \neq \lim_{n \to \infty} \left( \lim_{n \to \infty} \left( 1 + \frac{1}{n} \right)\right)^n = 1 $$

What am I missing here?

$\endgroup$
  • 4
    $\begingroup$ The limit of $\frac{2}{n-1}n$ is finite. That allows to take the inner limit first. $\endgroup$ – Daniel Fischer Aug 2 '14 at 16:08
4
$\begingroup$

It is not taking the limit "outside," really, but pushing it inside. So: $$\lim_{n\to\infty} f(n)^{g(n)} = (\lim f(n))^{\lim g(n)}$$

When both $\lim f(n)$ and $\lim g(n)$ exist.

This is true because (for some values $x,y$ at least) the function $(x,y)\to x^y$ is a continuous function. (Specifically, it is continuous at $(x,y)$ when $x>0$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.